A novel Fe recycling method from pickling wastewater producing a KFeS2 whisker for electroplating wastewater treatment. Issue 8 (11th June 2021) - Liang, Dongxu; Ji, Manhong; Zhu, Suiyi; Chen, Yu; Wang, Zhihua; Liu, Yanwen; Khan, Asghar; Ri, Kyonghun; Yu, Hongbin; Huo, Mingxin
Abstract : Pickling sludge was converted to a novel product of KFeS2 nanorods via a facile hydrothermal method that effectively removes heavy metals from electroplating wastewater. Abstract : Pickling is a common pre- or intermediate treatment in electroplating, enamelling, rolling and other processes. Here, pickling sludge was converted to a novel product of KFeS2 nanorods via a facile hydrothermal method that effectively removes heavy metals from electroplating wastewater. The pickling sludge was a mixture of weakly crystallised Fe in the form of irregular aggregates. The Fe content of the raw sludge was 35.9 wt% and the main impurities included aluminium, carbon and salt. After hydrothermal treatment, 74.6% of the Fe-containing compounds were converted to KFeS2 nanorod clusters with a diameter of 300 nm and lengths in the range of 2–5 μm. In the hydrothermal system, Fe 3+ was dissolved from the surface of the pickling sludge to form Fe(OH)4 −, which accelerated the formation of KFeS2 nanorod clusters. The prepared KFeS2 nanorods were effective in treating raw electroplating wastewater at pH 12.1, with removal rates of over 99% for Zn and Cu and 63.3% for Ni. These values were higher than those of poly ferric sulphate, poly aluminium chloride, Na2 S, raw sludge and activated carbon powder. The KFeS2 nanorods were metastable and hydrolysed spontaneously in alkaline electroplating wastewater. The generated Fe–SH groups on the surface formed a complex with metals, namely, Cu, Zn and Ni, and thus were removed with flocculation. Therefore, the KFeS2 nanorods generated from pickling wastewater recycling could be used as a prospective coagulant for heavy-metal removal in the treatment of alkaline electroplating wastewater.